Blood and oil - Earp, Jeremy; Morris, Scott; Michael T. Klare; Media Education Foundation (Northampton, MA : MEF, 2008)
The film unearhs declassified documents and highlights forgotten passages in prominent presidential doctrines to show how concerns about oil have been at the core of American foreigh policy for more than 60 years-rendering our contemporary energy and military policies virtually indistinguishable
Title from title screen
Based on the book'Blood and oil' by Michael T. Klare
Executive roducer, Sut Jhally ; co-producer, Andrew Killoyy ; editors, Andrew Killoy, Scott Morris ; camera, Andrew Killoy
With English subtitles
Keywords: Petroleum resources -- Political aspects -- United States; Energy policies -- United States